Platelet rich fibrin three-layer reconstruction of the sellar floor after endoscopic endonasal transsphenoidal approach: technical note and initial experience - Shah, Mukesch Johannes; Argiti, Katerina; Nakagawa, Julia M.; Stathi, Angeliki; Schönen, Emilia; Strahnen, Daniel; Joseph, Kevin; Straehle, Jakob; Neidert, Nicolas; Beck, Jürgen; Vasilikos, Ioannis (Frontiers in Surgery, 2024)
BackgroundCerebrospinal fluid (CSF) leakage frequently complicates endoscopic endonasal transsphenoidal pituitary resections, despite the use of lumbar drains, nasoseptal flaps, or commercial dura sealants. Managing this complication often requires revision surgery and increases the risk of infection. Platelet-rich fibrin (PRF), an affordable autologous biomaterial derived from the patient's blood through short, angulated centrifugation, contains growth factors and leukocytes embedded in a fibrin matrix. PRF exhibits regenerative properties in various surgical disciplines. This study assesses a three-layer sellar reconstruction method employing solid membranous (s-PRF) and high-viscosity injectable (i-PRF) forms of PRF.Materials and methodsWe present our initial experience on a series of 22 patients with pituitary macroadenomas. For all patients, an endoscopic transnasal transsphenoidal approach was selected. Following the resection of the pathology, sellar reconstruction was accomplished using a three-layer orthobiologic technique. A membranous s-PRF was utilized as an inlay inside the opened sellar floor, followed by a layer of injectable i-PRF finally covered with another s-PRF membrane over the top to the sellar corridor.ResultsIn all cases the implementation of the proposed three-layer PRF reconstruction strategy was feasible and safe. During the 12-month follow-up period there were no adverse effects reported associated with the PRF application. 77% (17/22) of the patients demonstrated intraoperatively a cerebrospinal fluid (CSF) leak (Esposito Grade 1–3). In total, the proposed PRF reconstruction effectively prevented postoperative CSF leaks in 95% of the patients and in 94% of those with an Esposito Grade 1–3. One of the two patients with intraoperative Esposito Grade 3 developed a CSF leak on the first postoperative day, which was successfully managed with a lumbar drain for 5 days.ConclusionSellar reconstruction after endoscopic endonasal transsphenoidal resection of pituitary adenomas with PRF is feasible and safe. The three layer PRF augmentation is a novel technique to prevent CSF-leakage.